Time-dependent seismic performance assessment of RC buildings exposed to corrosion. (January 2023) - Colak, Huseyin; Soyoz, Serdar
Abstract: Corrosion of reinforcing bars is one of the most notable reasons of the deterioration of reinforced concrete structures. The safety problems related to corrosion and the differences between the required and available budgets that will be used to repair the existing structures make the reliable prediction of the service-life of structures quite critical to optimize the costs by accurately prioritizing the rehabilitation projects and to overcome the structural safety problems. In this study, Reverse Monte Carlo Simulation is used to predict the future corrosion propagation of existing structures in accordance with the existing corrosion levels identified by site inspections. The novelty of the proposed method is to use existing corrosion levels of the reinforcements to increase the reliability of the expectations related to corrosion propagation in the future. In other words, experimental measurements are used as reference points according to which numerical models used to predict corrosion levels can be validated. A case study was performed using the proposed method for a corroded reinforced concrete building located in New Zealand and constructed in 1928. As the first step, the existing corrosion level of the building was used to predict how corrosion can propagate in the future. Afterwards, the numerical model of the building was developed using the OpenSees platform, and nonlinear static analyses were performed to assess the future seismic performance of the building. Results shows that the information about the existing corrosion levels of a building can be a valuable input to make reliable estimations for the future seismic performances of the existing buildings.